Do financing institutions consider operating performance in estimating cost of debt? - Muhammad Shahin Miah; Mohammad Ariful Islam; Md. Khaled Bin Amir (Future Business Journal)
Abstract This paper examines the relationship between firm performance and cost of debt. More specifically this paper empirically shows that fund providers charge lower cost on debt for highly performing companies compared to lower performing companies. We argue that the profitable companies are more resilient, and they have more survivable capacity which impacts on the pricing of the cost of debt. In contrast, lower performing companies are more prone to financial distress or may have higher chances of non-repayment of loans thereby fund providers charge higher interest to compensate the risks. Consistently, analyzing 547 firm year observations for the period of 2015–2019 we find that the cost of debt is significantly lower for the highly performing companies compared to the lower performing companies. The negative relation between the cost of debt and firm performance is highly pronounced in smaller companies compared to bigger companies. It suggests that fund providers create opportunities for smaller companies thereby results in balanced growth in the economy. Our results are robust to a set of alternative measures of firm performance. This study has several policy implications and contributions to the literature of the cost of debt in developing economies.